Local Drug Delivery to Bone Joints with Microspheres - Soundrapandian, Chidambaram; Poudyal, Adarsh Pratik (Journal of Drug Delivery and Therapeutics, 2019)
The concept of local drug delivery in the form of microspheres has potential for use as an alternative to conventional therapy strategies in the treatment of pain and inflammatory symptoms in case of certain bone and joint diseases. Commonly preferred treatment options for these symptoms (such as oral NSAIDs, analgesics, opioid pain medications) need to be frequently administered or applied and additionally, these suffer from multiple limitations. A prolonged release formulation of an NSAID i.e. Diclofenac Sodium, might prevent frequent administrations and improve the therapeutic outcome. In the current research, Diclofenac Sodium (DS)-loaded microspheres were prepared using thermal control and ionic cross-linking techniques. Calcium sulfate hemihydrate (CaSO4) was used in specific quantities to enhance the self-hardening property of the microspheres. An encapsulation efficiency and loading capacity of up to 90.24% and 61.41% respectively were achieved from the formulations. FTIR analysis indicated no major interactions between the active ingredient and the excipients used in the formulation process. In-vitro studies on the biodegradability of the microspheres disclosed that the microspheres showed a slow degradation pattern over time. Release study of the prepared microspheres revealed that the release of DS was prolonged achieving release of drug over a period of up to 11 days. The microspheres seem to fulfil the requisite criteria in-vitro. The results obtained suggest that DS-loaded microspheres have the potential for further investigation and development.Keywords: Local drug delivery, microspheres, bone and joint diseases, NSAIDs